Temporal Trends in Acute Adrenal Insufficiency Events in Children With Congenital Adrenal Hyperplasia During 2019-2022 - GÜRAN, TÜLAY (My University, 2024)
Background: It is unclear whether targeted monitoring of acute adrenal insufficiency (AI) related adverse events (AE) such as sick day episodes (SDEs) and hospitalization rate in congenital adrenal hyperplasia (CAH) is associated with a change in the occurrence of these events. Aim: Study temporal trends of AI related AE in the I-CAH Registry. Methods: In 2022, data on the occurrence of AI-related AE in children aged <18 years with 21-hydroxylase deficiency CAH were compared to data collected in 2019. Results: In 2022, a total of 513 children from 38 centers in 21 countries with a median of 8 children (range 1-58) per center had 2470 visits evaluated over a 3-year period (2019-2022). The median SDE per patient year in 2022 was 0 (0-2.5) compared to 0.3 (0-6) in 2019 (P = .01). Despite adjustment for age, CAH phenotype and duration of study period, a difference in SDE rate was still apparent between the 2 cohorts. Of the 38 centers in the 2022 cohort, 21 had also participated in 2019 and a reduction in SDE rate was noted in 13 (62%), an increase was noted in 3 (14%), and in 5 (24%) the rate remained the same. Of the 474 SDEs reported in the 2022 cohort, 103 (22%) led to hospitalization compared to 299 of 1099 SDEs (27%) in the 2019 cohort (P = .02). Conclusion: The I-CAH Registry can be used for targeted monitoring of important clinical benchmarks in CAH. However, changes in reported benchmarks need careful interpretation and longer-term monitoring. Key Words: 21-hydroxylase deficiency, adrenal insufficiency, adverse events, benchmark, congenital adrenal hyperplasia, sick day episodes, quality improvement, registry
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Endokrinoloji Ve Metabolizma; Clinical Medicine (Med); Clinical Medicine; Endocrinology & Metabolism; Endokrinoloji, Diyabet ve Metabolizma; Endocrinology, Diabetes and Metabolism; 21-hydroxylase deficiency; adrenal insufficiency; adverse events; benchmark; congenital adrenal hyperplasia; quality improvement; registry; sick day episodes; 21-hydroxylase deficiency; adrenal insufficiency; adverse events; benchmark; congenital adrenal hyperplasia; sick day episodes; quality improvement; registry